UGA SUNDANESE AHMADIYYA: LOCALITY OF MAHDIISM IN WEST JAVA - Jajang A Rohmana (UIN Raden Mas Said Surakarta, 2020)
Studies on Ahmadiyah have been very extensive both in their focuses and approaches. However, few scholars consider local culture as an important means of the Ahmadiyya movement. This study focuses on the use of local culture in the form of uga in the Sundanese Ahmadiyya tradition. Uga is an oral tradition of ancestor mystical prophecy in Sunda on the coming of an important change in a situation of crisis. This is an ethnographic study of the Sundanese uga among Ahmadiyya followers in Kuningan, Tasikmalaya, and Bandung. The uga of Ahmadiyya is then analyzed using an interpretive approach. This study shows that there are at least six ugas of Ahmadiyya in Bandung, Garut, Singaparna, Tasikmalaya, Ciamis, and Manislor Kuningan. These ugas represent a symbolic meeting point between the expectations of Sundanese on the change of a situation with the messianic beliefs in Ahmadiyya. Ugas can shape the experience, identity and strengthen the roots of mystical ideology of Ahmadiyya in Sundanese people. Hereby, the case of ugaSundanese Ahmadiyya is a strategy of acculturation of local culture which added other categorization in the context of Ahmadiyya movement in various countries around the world.